WALI NIKAH MENURUT PERSPEKTIF HADIS - Khoiruddin Nasution (State Islamic University North Sumatra, 2009)
Abstract: Merriage Guardian in Hadîth Perspective. Marriage guardian (walî al-nikâh) is one of the important issues in Islamic law. Of the four Sunni school of Jurisprudence, only Hanafî school of thought that gives room for the possibility of contracting marriage without guardian. This paper discusses the view of Hanafi school regarding the legality of marriage contract without guardian. The exposition is not only confined to describe contradictory views with the main stream school of Islamic jurisprudence and the majority of Indonesian Muslim, but also analyzes arguments developed by Hanafî school based on the Prophetic traditions, al-Qur’an and the views of the scholars. The author argues that the possibility of contracting marriage without the present of guardian is dependent on the question whether a person has capacity to act or not as found in prophetic tradition and Islamic Law genre.Kata Kunci: nikah, wali nikah, Sunnah